RESISTENSI DAERAH TERHADAP PROGRAM KELUARGA BERENCANA - Bunu, Helmuth Y. (PIRAMIDA, 2018)
The objective of this study is to describe: 1) the forms of resistance to family planning, 2) underlying factorsfactors of resistance, 3) resistance impact, and 4) the strategy to overcome the resistance. The study used a descriptive explanatory. This study was conducted In Midle Kalimantan at March-may 2016. Data were collected using participatory observation, interview, and documentation. Research objects are: persons, concept, place, and activities. Verification of data was done by credibility, transferability, dependability, and comfirmability criteria Data were analyzed using four qualitative research phases of Miles and Hubermann, namely data collection, data reduction, data classification, and making conclusions. Based on the research results, in general it can be concluded that: 1) the forms of resistance area to family planning begins with budget restrictions, 2) underlying factors-factors of resistance is due to the regional autonomy that gives authority to the regions to create development priorities, 3) resistance impact is increasing the population growth figures significantly, and 4)the strategy to overcome the resistance area that it needs to have intense coordination between central and local. family planning programs received maximum support from the region.